DEVELOPMENT OF THE NEUROMUSCULAR JUNCTION : I. Cytological and Cytochemical Studies on the Neuromuscular Junction of Differentiating Muscle in the Regenerating Limb of the Newt Triturus - Lentz, Thomas L. (The Rockefeller University Press, 1969)
Development of the neuromuscular junction on differentiating muscle was investigated in the regenerating limb of the newt Triturus. Motor end-plate formation begins when vesicle-filled axon terminations approach differentiating muscle cells that have reached the stage of a multinucleate cell containing myofibrils. Slight ridges or elevations occur on the muscle surface, and there is an increase in density of the cytoplasm immediately beneath the plasma membrane of the elevation. The axon becomes more closely approximated to the muscle cell and comes to lie in a shallow depression or gutter on the surface of the muscle. The surface ridges increase in length and constrict at their bases to form junctional folds. In the axon terminal, focal accumulations of vesicles are found where the axon contour projects slightly opposite the secondary synaptic clefts. Cholinesterase activity in the developing junctions was demonstrated by the thiolacetic acid-lead nitrate method. Enzymatic activity is not found on intercellular nerve fibers or the muscle surface prior to close approximation of axon endings and muscle. Eserine- and DFP-sensitive activity appears concurrently with morphological differentiation. Activity occurs in membranous tubulovesicles in the sarcoplasm subjacent to the neuromuscular junction and in association with the sarcolemma. The largest reaction deposits occur at the tips of the emerging junctional folds. Smaller and less numerous localizations occur on the axon membrane and within the axoplasm. It is concluded from these studies that the nerve endings have an inductive effect on both the morphological and chemical specializations of the neuromuscular junction.